Improved tet-responsive promoters with minimized background expression - Loew, Rainer; Heinz, Niels; Hampf, Mathias; Bujard, Hermann; Gossen, Manfred (BMC biotechnology, 2010)
The performance of the tetracycline controlled transcriptional activation system (Tet system) depends critically on the choice of minimal promoters. They are indispensable to warrant low expression levels with the system turned "off". On the other hand, they must support high level of gene expression in the "on"-state.